Islamic Humanism and Akhlaq Formation: A Conceptual Study in Islamic Education - Adi Saputra; Inayatillah Inayatillah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
Studies on Islamic humanism have largely been situated within normative philosophical discourse and have not been sufficiently operationalized within Islamic education, particularly in relation to faith development and moral formation. This study aims to analyze the concept of Islamic humanism and its implications for akhlaq formation and holistic learner development in the context of Islamic education. Employing a conceptual library research approach, this study examines primary and secondary sources, including the Qur’an, Hadith, works of classical and contemporary Muslim philosophers and scholars, as well as Islamic education literature. The analytical framework is grounded in Islamic anthropology, particularly the concepts of fitrah, human dignity (karāmah al-insān), and akhlaq as the foundation of education. The findings indicate that Islamic humanism is theocentric in nature, positioning human dignity as inseparable from moral and spiritual responsibility to Allah SWT. From an Islamic education perspective, Islamic humanism contributes to faith development, moral cultivation, and holistic learner formation encompassing spiritual, moral, intellectual, and social dimensions. This study offers an original conceptual contribution by positioning Islamic humanism not merely as a philosophical discourse but as a pedagogical framework relevant to akhlaq and character education in contemporary Islamic education.